„Transition to farming in the Baltic” (sprawozdanie z konferencji) - Domańska, Lucyna (Acta Universitatis Lodziensis. Folia Archaeologica, 1996)
The conference organized by the Department of Archaeology of Łódź University and by the Institute of Archaeology and Prehistory of Sheffield University (Great Britain) was held on 14th-17th September, 1992. The conference dealt with the „Transition to fanning in the Baltic” and its main purpose was to exchange experience in the research on the beginnings of productive economy in the Baltic Sea region. The following subjects were discussed: Social and economic organization of the late Mesolithic hunter-gatherers. Contacts between the late Mesolithic hunter-gatherers and early farming societies. Cultural changes and responses within the hunter-gatherers societies occurring through contact with early farming societies. Management of non-domesticated plant and animal resources by late Neolithic hunter-gatherers. Health and demographic changes at the agricultural transition. Explanations for the adoption of farming. Continuity and change at the agricultural transition: the case of acculturation of hunter-gatherers by early farming communities of the adoption of farming by the resident hunter-gatherers.